Modern problems of onomastics in the sphere of trademarks (Eurasian Journal of Philology Science and Education, 2019)
The article touches upon the peculiarities of teaching onomastics as an academic discipline at highereducational institutions. It is concerned with a wide range of problems connected with proper namesconstituting the onomastic space of any language. The new tendencies characterizing the developmentof onomastics indicate that the research in this area has broadened its scope and various categories ofnames that were not previously studied are in the focus of attention of scholars. It refers to commercialnomination orientated on obtaining profit and regarded as linguistic naming of different goods, products,institutions, enterprises. In this case, the issues related to linguistic expertise of commercial names are ofparticular relevance, since in the conditions of market competition the verbal designations of trademarkscan be close or similar in sound form and graphics, which can lead to their confusion. The article considers methods used in linguistics to determine the degree of identity or difference of similar trademarks.The methodology of linguistic expertise is described on the particular example of comparing the verbaltrademarks АССУ (Cyrillic script letters) and A’SU (Latin script letters) used to name water beveragesproduced in Kazakhstan.